GAMBARAN HASIL PEMERIKSAAN LAJU ENDAP DARAH (LED) MENGGUNAKAN METODE WESTERGEN PADA PASIEN RAWAT JALAN - Susiyanti, Susiyanti; Mawarti, Listina; Ilmi, Ana Kholfatin (JURNAL KESEHATAN TERAPAN, 2021)
Background: ESR is one of the routine blood parameters that is often requested as a complement to other haematological examinations. Purpose: To determine the description of the results of the blood sedimentation rate (LED) using the Westergen method on outpatients. Methods: This type of research is quantitative using cross sectional research design with sampling techniques using accidental sampling obtained a sample of 82 respondents. Results: that the results of the LED examination using the Westergren method on outpatients found 11 people (22%) with normal ESR, and 39 people (78%) with abnormal ESR. Suggestion: input material in improving the quality of examinations and services in the health sector, so that it is more detailed and thorough in carrying out LED examinations using the Westergen method. Key words: Precipitation Rate (LED)